Investigating the compatibility of affordable housing with sustainability criteria: a conceptual framework - Olanrewaju, AbdulLateef; Yeow, Seong Tan; Tat, Lim Lee; Ayob, Mohd Fairullazi; Ang, Salem (WMIT Group Sdn. Bhd., 2016)
While efforts are being made to close the housing gap, sustainability factors are not being considered as an essential element in the affordable housing delivery. However, affordable housing could be part of the solutions or threats to sustainability. Today sustainability requirement has become the fourth dimension of the value system of the modern clients/users aside the traditional cost, time and quality dimensions. Households are currently demanding for sustainable housing. The sustainability credential of the developers and contractors are now being challenged. Researches on the roles of housing towards sustainability are aplenty. However, existing research and practices have not only treats sustainability and affordability as mutually exclusive, but also adopted the ‘incremental’ and technology approaches. But while the market for sustainable affordable housing is small a major issue is that the design professionals are not familiar with the responsibilities and duties they are supposed to play in greening the affordable housing delivery. These are limiting the contributions of affordable housing to the sustainability paradigms. Through literature review, the study reported in this paper evaluates the responsibilities and duties of the design and construction teams in the delivery of sustainable affordable housing. The RIBA Plan of Work was used in framing the duties and responsibilities of the design team in the sustainable affordable housing delivery. The research is useful to the policy makers, developers, manufacturers, contractor, rating agencies, suppliers and householders and users. This research aims to produce a prototype housing delivery model in order to facilitate systemic delivery of affordable housing that complied with sustainability.